A new look at historical monetary policy (and the great inflation) through the lens of a persistence-dependent policy rule. (24th April 2020) - Ashley, Richard; Tsang, Kwok Ping; Verbrugge, Randal
Abstract: The origins of the Great Inflation, a central 20th-century U.S. macroeconomic event, remain contested. Prominent explanations are poor inflation forecasts or inaccurate output gap measurement. An alternative view is that the Federal Open Market Committee (FOMC) was unwilling to fight inflation, perhaps due to political pressures. Here, we sort this out via a novel econometric approach, disaggregating the real-time unemployment and inflation time series entering the FOMC historical policy reaction-function into persistence components, using one-sided Fourier filtering; this implicitly estimates the unemployment gap in actual use. We find compelling evidence for (economically interpretable) persistence-dependence in both variables. Furthermore, our results support the "unwilling to fight" view: the FOMC's unemployment gap responses were essentially unchanged pre- and post-Volcker, while its inflation responses sharpened markedly starting with Volcker.